Implikasi Penataan Wisata Alam dan Spiritual Bunut Bolong Desa Manggissari Kabupaten Jembrana - Mahardika, Gede; Hadriani, Ni Luh Gede (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
Bunut Bolong as a tourist attraction in Manggissari Village, Jemrana Regency has not been arranged optimally, so the role of the local community, traditional villages and local government is needed to organize Bunut Bolong as a better tourist attraction. The aim of this research is to determine the tourist attraction of Bunut Bolong in Manggissari Village, Jemrana Regency. This research uses a descriptive qualitative method using observation, interview and documentation study data collection methods. The results of this research show that the forms of Bunut Bolong tourist attractions include: first, forms of cultural tourism such as cultural relics of the past in the form of manger stone sarcophagi which are believed to have existed from the megalithic era which is a tourist attraction, Pura Bhujangga Sakti Luwih. Second, the form of spiritual tourism, namely Bunut Bolong, has a magical aura that is believed by the surrounding community. Third, a form of ecotourism, namely Bunut Bolong, has beautiful views with expanses of clove and coffee gardens owned by the surrounding community.